Abnormal topological characteristics of brain white matter network relate to cognitive and emotional deficits of non-small cell lung cancer (NSCLC) patients prior to chemotherapy. (3rd April 2022) - Liu, Siwen; Yin, Na; Ma, Rong; Cao, Haixia; Jing, Changwen; Zhang, Yuan; Chen, Dan; Zhang, Junying; Wu, Yang; Feng, Jifeng; Wu, Jianzhong
Abstract: Introduction: Cancer and chemotherapy are correlated with brain functional and structural changes in cancer patients, which may lead to cognitive dysfunction. However, little is known about the structural abnormalities of brain in patients with non-small cell lung cancer (NSCLC). The aim of this study was to explore the topological properties within the brain white matter network of NSCLC patients prior to chemotherapy. Methods: To explore the neurobiological biomarkers of NSCLC, brain magnetic resonance imaging (MRI) data were acquired in 24 non-nervous system metastatic NSCLC patients and 25 matched healthy controls. The topological properties of the brain structural networks of NSCLC were measured by the parameters of local and global efficiency. Results: Treatment-naïve NSCLC patients showed cognitive and emotional deficits. In addition, NSCLC patients also exhibited decreased global efficacy in the left inferior frontal gyrus (triangular part), left inferior frontal gyrus (orbital part), right rolandic operculum, right gyrus rectus, right lenticular nucleus (putamen), left superior temporal gyrus and right inferior temporal gyrus. Decreased local efficacy were found in the left middle frontal gyrus (orbital part) and left superior temporal gyrus in NSCLC patients. Moreover, the aberrant brain regions were associated with the impaired cognitiion and emotion of NSCLC patients. Conclusion: Overall our results suggested that altered local and global efficiency of brain white matter network were associated with cancer-induced cognitive and emotional deficits of NSCLC patients. These findings demonstrated that disrupted topological characteristics of the brain network might underlie the impaired cognition and emotion in NSCLC.